“FROM INDIVIDUAL WELL-BEING TO NATIONAL PROGRESS: THE PHILOSOPHICAL MEANING OF HEALTHY LIVING IN NEW UZBEKISTAN” - Gadoyeva Lobar Ergashevna (Western European Studies, 2025)
This article explores the philosophical significance of healthy living in the context of New Uzbekistan’s social transformation. As the country implements comprehensive reforms aimed at strengthening human capital, the concept of a healthy lifestyle becomes more than an individual choice—it evolves into a cultural, ethical, and philosophical imperative. Drawing on classical and contemporary philosophical frameworks, as well as anthropological theories of human development, the study examines how health-related values shape the moral consciousness of citizens and contribute to national progress. The analysis demonstrates that a healthy lifestyle in New Uzbekistan represents an integrated worldview, linking personal wellbeing, social responsibility, and collective modernization
Keywords: Healthy lifestyle; New Uzbekistan; philosophical meaning